Characterization and Modeling of Power Electronics Device - Tandjaoui Mohammed Nasser; Benachaiba Chellali; Abdelkhalek Othmane; B. Denai; Y. Mouloudi (Institute of Advanced Engineering and Science, 2014)
During the three decades spent, the advances of high voltage/current semiconductor technology directly affect the power electronics converter technology and its progress. The developments of power semiconductors led successively to the appearance of the elements such as the Thyristors, and become commercially available. The various semiconductor devices can be classified into the way they can be controlled, uncontrolled category such as the Diode when it’s on or off state is controlled by the power circuit, and second category is the fully controlled such as the Metal Oxide Semiconductor Field Effect Transistor (MOSFET), and this category can be included a new hybrid devices such as the Insulated Gate Bipolar Transistor (IGBT), and the Gate Turn-off Thyristor (GTO). This paper describes the characteristics and modeling of several types of power semiconductor devices such as MOSFET, IGBT and GTO.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.4318